Intratendinous ganglion cyst of the extensor digitorum longus tendon: A case report. (June 2016) - Robinson, Cal; Kocialkowski, Cezary; Bhosale, Abhijit; Pillai, Anand
Highlights: First reported case of an intratendinous ganglion of the EDL tendon. Increased risk of spontaneous tendon rupture warrants a lower operative threshold. Aspiration, corticosteroid injection and cyst puncture should be avoided. Surgical options should address recurrence risk and tendon functional demands. Abstract: Introduction: Ganglion cysts are benign lesions, common in the hand and wrist. Intratendinous ganglion, however, are rare. We present the first reported case of an intratendinous ganglion cyst in an extensor digitorum longus (EDL) tendon of the foot. Case report: A 35-year old presented with a left-sided painful dorsolateral foot swelling. Ultrasound suggested a ganglion cyst in proximity to the EDL tendon of the 5th toe. Two distinct swellings were identified on surgical exploration, including a 6 × 1 cm ganglion lying within the EDL tendon substance that had resulted in tendon splitting. The lesions were excised and EDL tendon repaired. Histological analysis confirmed that both lesions were ganglion cysts. Post-operative recovery was uneventful. Discussion: Intratendinous ganglion cysts are rare lesions that pose a unique set of diagnostic and treatment challenges. Unlike conventional ganglion, their diagnosis may not be possible until surgical exploration. They have been reported to increase the risk of spontaneous tendon rupture. As such, a lower operative threshold should be applied to prevent their progression. A high index of suspicion should be applied to any ganglion reported radiologically to be in close contact with tendons. If diagnosed upon surgical exploration, it is essential that the operating surgeon is prepared to appropriately modify the procedure to involve primary tendon repair, tendon transfer or tenodesis.